Austrians-in-the-World. Conversations and Debates About Planning And Development - Friedmann, John (European Spatial Research and Policy, 2014)
John Friedmann has taught at MIT, the Pontifical Catholic University of Chile, UCLA, the University of Melbourne, the National University of Taiwan, and is currently an Honorary Professor in the School of Community and Regional Planning at the University of British Columbia in Vancouver, Canada. Throughout his life, he has been an advisor to governments in Brazil, Venezuela, Chile, Mozambique, and China where he was appointed Honorary Foreign Advisor to the China Academy of Planning and Urban Design.